Jajarkot Diarrhoea Outbreak, 2009 - Nepal Health Research Council (NHRC) (Nepal Health Research Council, 2012)
Introduction: The information on outbreak was first noticed when the public media highlighted about a death and large number of diarrhea cases in Rokaya village development committee (VDC) of Jajarkot district on 20th Baisakh 2066. The Rapid Response Team was mobilized on 21 Baisakh 2066 in the same VDC and treated 224 patients. The mortality reduced to zero by the end of Jestha 2066. According to the District Public Health Office Jajarkot and the public media, the morbidity and mortality due to diarrhea started increasing from the third week of Ashad. The Nepal Health Research Council (NHRC) called a meeting and felt the need to specify the agents responsible for outbreak by conducting an outbreak investigation from research perspective. The Executive Chairman chaired the meeting and formed a 3 member team for outbreak investigation. The members of working team were Dr. Gajananda Prakash Bhandari (Epidemiologist, NHRC), Mr. Umesh Ghimire (Research Assistant, NHRC) and Dr Sameer Mani Dixit (Director, CMDN). This team was responsible to collect epidemiological data and stool specimens to know the epidemiological pattern of disease as well as confirmation of diagnosis. A laboratory technician joined the team in Jajarkot with required transport media to collect stool specimen. Epidemiological data were analyzed by the team of Nepal Health Research Council and the laboratory samples were diagnosed by National Public Health Laboratory.